The IPY Project "The Dynamic Continental Margin Between the Mid-Atlantic-Ridge System (Mohns Ridge, Knipovich Ridge) and the Bear Island Region" - Schweitzer, J.; Guterch, A.; Krüger, F.; Schmidt-Aursch, Mechita C.; Bear Island, Project Group (2008)
In 2007, we began with an active and passive seismological experiment along the continental margin of the Barents Sea near Bear Island and the mid-Atlantic along the Knipovich Ridge. The field experiments comprise the installation and parallel operation of several seismic instruments during 2007-2008. The aims of this study are the Earth's structure and dynamics at the continental margin from its top sedimentary cover to its imprint in the upper mantle. In this region the margin includes an extremely thick sedimentary wedge and steep slopes, with at least one major paleo-fracture zone cutting through the wedge. Recent studies in this area indicate very low seismic velocities in the lithosphere, which may be explained by subcrustal extension of Mohns Ridge. The stress field undergoes an extensional-compressional transition in the region of the margin. It is therefore of particular interest to understand the structural architecture, the stress and the dynamics of the whole region because of its natural hazard exposure, and the processes involved in formation of the margin and opening of the Atlantic. The collection of deep seismic sounding data, and detailed monitoring and analysis of the seismicity between margin and mid-Atlantic ridge system, using temporary broadband stations, are necessary for providing such information. Data from existing seismic stations in the European Arctic will also be analysed. In September 2007, 12 OBSs and two new bb-sensors were installed at the Polish Polar Station Hornsund and on Hopen Island, respectively. For 2008, the installation of a small array on Bear Island is planned as well as conducting activeseismic refraction/reflection experiments along two profiles crossing the mid-Atlantic ridge systems, the margin and Bear Island. The profiles will be supplemented with 40 short-period stations on Bear Island and 15 OBSs to retrieve the 3D lithospheric structure.